Forensic Evaluation of a Single Episode of a Disorder of Arousal in a Sleepwalking Defense: Cognitive Function Versus Prior Clinical History - Mark R. Pressman (Sleep Science)
Introduction The clinical diagnosis of disorders of arousal (DOA) is based primarily on a clinical history including amnesia for episodes. The presence of amnesia means the patient cannot provide direct evidence. In a forensic setting, when the defendant has been charged criminally with violent actions or sexual related assaults allegedly during sleep, a sleepwalking defense may be presented. As opposed to clinical history, the prosecution generally focuses on the single episode of alleged DOA that resulted in the criminal charges against the defendant. The prosecution will argue that this episode of complex behavior was not consistent with a DOA. A past history of purported episodes is not proof that a recent single episode must be a DOA. However, most sleepwalking defenses rely heavily on standard clinical evaluations despite the fact they have no direct connection with the current criminally charged episode.